Immunophenotypic features of dedifferentiated endometrial carcinoma – insights from BRG1/INI1‐deficient tumours. Issue 4 (5th July 2016) - Hoang, Lien N; Lee, Yow‐Shan; Karnezis, Anthony N; Tessier‐Cloutier, Basile; Almandani, Noorah; Coatham, Mackenzie; Gilks, C Blake; Soslow, Robert A; Stewart, Colin J R; Köbel, Martin; Lee, Cheng‐Han
Abstract : Aims: Dedifferentiated endometrial carcinoma (DDEC) is defined by the presence of an undifferentiated carcinoma together with an endometrioid carcinoma. Inactivation of SMARCA4 ( BRG1 ) and inactivation of SMARCB1 ( INI1 ) were recently described as potential mechanisms underlying the histological dedifferentiation. The aim of this study was to characterize the immunophenotypic features of DDECs, particularly in cases with prototypical histological and molecular features (BRG1/INI1 deficiency). Methods and results: We evaluated PAX8, oestrogen receptor (ER) and p53 immunostaining in the endometrioid and the undifferentiated components of 20 BRG1/INI1‐deficient DDECs and 15 BRG1/INI1‐intact DDECs, and compared the results with those of 23 grade 3 endometrioid carcinomas. The differentiated endometrioid component was positive for PAX8 and/or ER in 19 of 20 BRG1/INI1‐deficient DDECs, whereas the corresponding undifferentiated component of all 20 tumours showed a complete absence of PAX8 and ER staining. All except one of the BRG1/INI1‐deficient tumours showed a wild‐type p53 staining pattern. PAX8 and ER expression in the undifferentiated component was absent in 67% and 80% of BRG1/INI1‐intact DDECs, respectively, whereas 47% of the BRG1/INI1‐intact DDECs showed a mutated p53 staining pattern. In comparison, absent PAX8 expression and absent ER expression were each observed in the more solid area of 48% and 48% of grade 3 endometrioid carcinomas. Conclusions: The consistent absence of PAX8 and ER expression in molecularly defined (BRG1/INI1‐deficient) DDECs suggests that the loss of PAX8 and ER expression is a fundamental feature of dedifferentiation. The frequent findings of a mutated p53 staining pattern in BRG1/INI1‐intact DDECs indicate that BRG1/INI1‐intact DDECs may be biologically different from BRG1/INI1‐deficient tumours.